The Prostate Care Questionnaire for Carers (PCQ-C): reliability, validity and acceptability - Steward William; Colman Andrew M; Agarwal Shona; Tarrant Carolyn; Baker Richard; Sinfield Paul; Kockelbergh Roger; Mellon John K (BMC, 2009)
Abstract Background Patient experience is commonly monitored in evaluating and improving health care, but the experience of carers (partners/relatives/friends) is rarely monitored even though the role of carers can often be substantial. For carers to fulfil their role it is necessary to address their needs. This paper describes an evaluation of the reliability, validity and acceptability of the PCQ-C, a newly developed instrument designed to measure the experiences of carers of men with prostate cancer. Methods The reliability, acceptability and validity of the PCQ-C were tested through a postal survey and interviews with carers. The PCQ-C was posted to 1087 prostate cancer patients and patients were asked to pass the questionnaire on to their carer. Non-responders received one reminder. To assess test-retest reliability, 210 carers who had responded to the questionnaire were resent it a second time three weeks later. A subsample of nine carers from patients attending one hospital took part in qualitative interviews to assess validity and acceptability of the PCQ-C. Acceptability to service providers was evaluated based on four hospitals' experiences of running a survey using the PCQ-C. Results Questionnaires were returned by 514 carers (47.3%), and the majority of questions showed less than 10% missing data. Across the sections of the questionnaire internal consistency was high (Cronbach's alpha ranging from 0.80 to 0.89), and test-retest stability showed moderate to high stability (intraclass correlation coefficients ranging from 0.52 to 0.83). Interviews of carers indicated that the PCQ-C was valid and acceptable. Feedback from hospitals indicated that they found the questionnaire useful, and highlighted important considerations for its future use as part of quality improvement initiatives. Conclusions The PCQ-C has been found to be acceptable to carers and service providers having been used successfully in hospitals in England. It is ready for use to measure the aspects of care that need to be addressed to improve the quality of prostate cancer care, and for research.